SOCIAL EXCHANGE THEORY : Telaah Konsep George C. Homans Tentang Teori Pertukaran Sosial - Shokhibul Mighfar (LP2M Universitas Ibrahimy, 2015)
Homans said that every human behavior has a basic psychological explanation. Homans also likened between social behavior and individual behavior. Social exchange theory is on a micro-level. Homans developed it more specific. by asking some scientific propositions: the success proposition, the stimulus proposition, the value proposition, the deprivation-satiation proposition, the Aggression-Approval proposition, the Rationality proposition. Many critics from sociologists to Homans: first, it didn’t have the most essential of human, the second view is Man Economies is not realistic to see the world as a system that towards the exchange of balanced, third, Views Distributive Justice in Power and Justice is less precise, slavery, less salary; war can be reduced by social exchange theory?